Development of Mathematics Learning Devices by Applying Problem Based Learning to Increase Students Mathematical Solving Skills of Class VII Junior High School - Rahmi Fitria; Nahor Murani Hutapea; H. Zulkarnain H. Zulkarnain (Universitas Riau, 2020)
This research was motivated by the low ability of Mathematical Problem Solving (KPMM) of students. In order to improve KPMM, teachers can do designing the learning process. This study aims to develop mathematical learning tools that are valid, practical and effective. The development model used the Borg and Gall model. The research instrument consisted of syllabus validation sheets, lesson plane (RPP), student worksheet (LKPD), observability of implementation, student questionnaire responses and KPMM test instruments. The result shows the mathematics learning kit using the PBL model was already valid which is for the syllabus was 85.41%, RPP was 85.11%, LKPD was 88.67% and the test instrument was 81.71%. The learning kit fulfills the practicality requirements in large group trials with an average questionnaire of students responses of 91.99% and an average of 94.58%. Effective mathematics learning tools is to improve KPMM of students with student learning outcomes that is based on the achievement of KKM with the percentage of completeness reached is 88.24%. Development of learning tools can significantly improve students mathematical problem solving abilities at a significant level of P = 0,000 with α = 0.05. Thus, it can be concluded that the development of mathematics learning tools by applying problem based learning can improve students mathematical problem solving abilities